Peningkatan kualitas pendidikan guru sekolah dasar melalui penguatan profil pelajar Pancasila di era digitalisasi - Aghfar, M. Sambuaga (Maliki Interdisciplinary Journal, 2024)
This study focuses on improving the quality of elementary school teacher education through the strengthening of the Pancasila Student Profile in the digital era. Enhancing student character is a primary goal in achieving the objectives of the national education system as mandated by Law No. 20 of 2003 on the National Education System. Character education through the application of Pancasila values is expected to shape students who are devout, pious, noble in character, and globally competent. In this context, teachers play a crucial role as change agents who instill character values in students. Through training and workshops, teachers are trained to develop project-based learning that integrates Pancasila values. The challenges in the digital era, such as the decline in student character values, require teachers to continually enhance their professionalism and skills. Therefore, improving the quality of education through the strengthening of the Pancasila Student Profile is a critical step in creating a generation with strong character and high integrity, in line with the goals of national education.